Nucleopolyhedrovirus Coocclusion Technology: A New Concept in the Development of Biological Insecticides - Williams, Trevor; López-Ferber, Miguel; Caballero, Primitivo (Frontiers in Microbiology, 2022)
Nucleopolyhedroviruses (NPV, Baculoviridae) that infect lepidopteran pests have an established record as safe and effective biological insecticides. Here, we describe a new approach for the development of NPV-based insecticides. This technology takes advantage of the unique way in which these viruses are transmitted as collective infectious units, and the genotypic diversity present in natural virus populations. A ten-step procedure is described involving genotypic variant selection, mixing, coinfection and intraspecific coocclusion of variants within viral occlusion bodies is described. Using two examples, we demonstrate how this approach can be used to produce highly pathogenic virus preparations for pest control. As restricted host range limits the uptake of NPV-based insecticides, this technology has recently been adapted to produce custom-designed interspecific mixtures of viruses that can be applied to control complexes of lepidopteran pests on particular crops, as long as a shared host species is available for virus production. This approach to the development of NPV-based insecticides has the potential to be applied across a broad range of NPV-pest pathosystems.